PEMBENIHAN IKAN KOI (Cyprinus carpio) SECARA ALAMI DI MINA SUMBER UTAMA KOI - Ritonga, Lusiana BR; Nasuki, Nasuki; Sari, Lutfia Indah (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
Koi fish is one of the freshwater ornamental fish that has the potential to be developed and has important economic value. opening the market for koi fish seeds is quite high, so the availability of seeds must be available continuously. One way to produce seeds is by spawning. The main parameters observed in this study were fertilization rate, hatching rate and survival rate. The value of the fertilization rate in spawning 1 was 79 and spawning II was 80%. The hatching rate in spawning I was 73% and in spawning II was 87%. The survival rate for spawning 1 was 96% and spawning II was 79%.